PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK DI KELAS VIII - Ningrum, Adella Sekar (Departemen Matematika, 2023)
Mathematical mastery necessitates a proficiency in problem-solving. Lesson plans are not always the most effective method to help students develop these abilities. According to studies, problem-solving skills are still deficient among learners. Based on the results of examinations administered to eighth graders, this was also observed at SMPN 7 Padang. Realistic Mathematics Education (PMR) is an approach for overcoming this issue. The purpose of this study is to determine whether students who learn using the PMR method have superior mathematical problem-solving skills compared to those who learn using the conventional method. This study also seeks to describe the development of students' mathematical problem-solving skills following the implementation of the PMR method. This study employs a quasi-experimental and descriptive design with a non-equivalent posttest-only control group. The research population consisted of all eighth-grade SMPN 7 Padang students. As research instruments, descriptive-formatted tests and quizzes were utilized. According to data analysis, students who learn using the PMR approach have superior problem-solving abilities compared to students who learn using conventional approaches, and after using the PMR approach, students' mathematical problem-solving abilities improve.Keywords – Conventional Approach, Realistic Mathematics Education Approach, Problem Solving Ability